La inteligencia emocional aplicada en las organizaciones (2013)
The main premise of this model is that emotional intelligence is that the personal and professional success requires the understanding and management of one’s emotions, self-motivated and to understand and manage the emotions of others. The actual world has demonstrated that the successful people are not characterized based on their rational intelligence or on their intellectual coefficient. On the contrary, the most common features within the successful leaders and managers are their personal abilities.